Exploring the Effectiveness of Computer Activinspire Software on Students Academic Achievement in Mathematics - Dantani, Wushishi, Ibrahim; Grace , Durodola, Temilolu (African Journal of Education,Science and Technology (AJEST), 2016)
This study explores the effectiveness of Computer ActivInspire software on students’ achievement in learning mathematical concepts that have to do with graph. The research uses a Pretest – Posttest randomized equivalent group design. The population of Senior Secondary School (SSS) class 3 students is 6,147 spread across Minna Metropolis. Four schools were chosen using multistage sampling within Minna Metropolis and the sample of the study consisted of 120 randomly selected students. The experimental group was taught using the activinspire software, while the control group was taught using the conventional method. The research instrument used was the Mathematics Achievement Test (MAT). This was validated by experts and were certified to have content validity. The reliability coefficient of 0.83 was obtained. The data collected after 6 weeks of application was analysed using Analysis of Variance Statistics with the aid of SPSS Version 16.0. Two hypotheses were tested at 0.05 significant level. The results showed that there was significant difference between experimental and control groups’ achievement. This difference is in favour of the experimental group which had lessonstaughtthe ActivInspire Software. The results also showed that there was no significant difference in the achievement of male and female students taught using the activinspire software. It was recommended that Computer ActivInspire software should be explored by teachers for enhancing their teaching. The use of the computer ActivInspire software would also help in bridging the perceived gender disparity in students understanding of mathematical concepts. The government should promote the use of the software through organizing seminars, workshops and induction courses for science teachers.